UTAUT model: Intent to use Mangusada app with technophobia as moderator - I Gusti Ayu Novitasari; Ni Luh Ulansari Manikan Widayani (Annals of Management and Organization Research, 2025)
Purpose: This study employs the Unified Theory of Acceptance and Use of Technology (UTAUT) model to examine the utilization of the Mangusada Mobile Application within the context of technophobia. It aims to analyze how performance expectancy, effort expectancy, facilitating conditions, habit, and trust influence behavioral intention and use behavior of the application. Methodology: The study involved 145 users of the Mangusada Mobile Application. Data were analyzed using the P artial Least Squares Structural Equation Modeling (PLS-SEM) technique with SmartPLS version 4.0. Results: Findings reveal that performance expectancy, effort expectancy, facilitating conditions, habit, and trust significantly and positively affect behavioral intention and use behavior. However, technophobia does not significantly moderate the relationships between performance expectancy, effort expectancy, and facilitating conditions with behavioral intention. Conclusion: The results indicate that users’ behavioral intention and usage of Mangusada Mobile are primarily driven by perceived performance, ease of use, available support, habitual engagement, and trust. Fear of technology does not appear to be a major deterrent. Limitations: The study is limited by its relatively small sample size, single research location, and the exclusive use of technophobia as a moderating variable. Future research should incorporate larger and more diverse samples and consider additional moderating factors such as digital literacy and perceived risk. Contribution: This study contributes to the UTAUT literature by integrating technophobia as a moderating factor and providing insights into technology acceptance in healthcare mobile applications.